Pregnancy-Induced Post-Natal Back Pain - Sushmita Neog (International Journal of Women's Health Nursing And Practices, 2025)
Pregnancy-induced post-natal back pain (PNBP) is a common condition that affects many women following childbirth, significantly impacting their quality of life and physical functioning. The physiological and anatomical changes during pregnancy, such as weight gain, altered posture, and hormonal changes, contribute to the onset of back pain. As the body prepares for delivery, the pelvis and spine undergo structural shifts that can strain the muscles and ligaments supporting the lower back. After delivery, the recovery process may be complicated by the demands of infant care, leading to persistent discomfort. This article explores the underlying causes, risk factors, and treatment options for pregnancy-induced post-natal back pain. It reviews the role of hormonal changes, muscle imbalances, and postural adjustments that contribute to the development of back pain in the post-natal period. The review also examines the impact of factors such as previous back problems, prolonged labor, and the use of epidural anesthesia, which can exacerbate post-natal back pain. Additionally, the article highlights effective management strategies, including physical therapy, core strengthening exercises, and ergonomic modifications, aimed at relieving pain and improving functional recovery. Psychological support, rest, and proper posture while breastfeeding or lifting the infant are also essential components of treatment. The role of healthcare providers in educating new mothers on post-natal back care is emphasized to prevent long-term complications. In conclusion, while pregnancy-induced post-natal back pain is common, it is often manageable with a multidisciplinary approach. Early intervention and tailored physical therapy programs are crucial in ensuring proper recovery, minimizing pain, and restoring overall well-being for new mothers.
Keywords: Pregnancy-induced back pain; back pain management; core strengthening; physical therapy; post-natal recovery; postural adjustments